“Structural characterization of protein isolates obtained from chia (Salvia hispanica L.) seeds” - López, Débora Natalia (2018)
Chia protein isolates (CPI) were obtained through isoelectric precipitation under two different conditions in order to compare their structural properties. Extraction was carried out at pH 10 or 12, whereas precipitation pH was fixed at 4.5. Samples were named as CPI10 or CPI12, according to their extraction pH (10 or 12, respectively). The recovery of chia proteins was higher when the extraction was carried out at pH 12 (17% for CPI12 and 13% for CPI10); however, CPI12 protein content (775 g/kg) was slightly lower than CPI10 protein content (782 g/kg). Both samples showed similar SDS-PAGE pattern. Protein dispersions of both isolates led to highly stabilized particles due to their negative ζ potential (around −54 mV). CPI10 has a higher proportion of small particles in suspension, revealed by a lower d3,2 value. Spectroscopic techniques showed that CPI10 presented higher content of β-helix than CPI12, resulting in higher thermal stability. This observation was supported by FT-IR spectroscopy since CPI10 presented less unordered structure than CPI12. The energy of endotherms obtained in CPI12 was considerably lower than in CPI10. Extraction at higher alkaline conditions led to a more denatured protein conformation with a higher content of random structure (18.1% for CPI10 and 22.9% for CPI12).